OBSERVATION OF CHILDREN WITH HIV_INFECTION AND CHILDREN WITH PERINATAL CONTACT WITH HIV-INFECTION IN SPECIALIZED CHILDREN'S HOME - V.I. Orel; N.D. Dzhangavadze; V.M. Siletskaya (Вопросы современной педиатрии, 2009)
This article presents data of prevalence of HIV-infection in Russian Federation and St.-Petersburg. Main attention was given to problem of HIV-infection in fertile women, ways of viral transmission. Authors note that role of viral transmission by sexual contact in last years became more actual. The state of health in children, born from HIV-positive women was characterized by basic indices: physical and psychical development, morbidity, quality of life. Authors pay attention on problem of social orphan hood in children with perinatal contact with HIV-infection. Key words: HIV, children, prevalence, indices of health. (Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(3):14-17)